Sustainability Reporting Disclosure on Industry in Indonesia - Heni Hardianti; Lia Uzliawati; Windu Mulyasari (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to analyze Sustainability Reporting disclosure in different industry type. This study also examine the effect of Sustainability Reporting on company value in public companies listed on the Indonesia Stock Exchange. The industry type consisted 8 industry are agriculture; mining; basic industry and chemical; miscellaneous industry; consumer goods industry; property, real estate, and building construction; infrastructure, utility, and transportation and trade, service, and investment. Sustainability Reporting variable was measured by SRDi and company value variable was measured by Tobin's Q. This study used a quantitative method, data obtained from annual report, financial report, and sustainability report from 2015-2019. Determination of the sample used slovin and purposive sampling techniques. Determination of the sample used slovin and purposive sampling methods. This study was analyzed using the ANOVA test with One Way Analysis of Variance and multiple regression analysis. Data was analyze by software IBM SPSS V.25 for windows. The results of this study show that the level of Sustainability Reporting disclosure in each industry is different, both in terms of the number of items and in terms of the aspects disclosed. However, Sustainability Reporting disclosure has no effect on company value.